Characterization of convective rain in Klang Valley, Malaysia - Ahmad, Nordila (2008)
Storms of convective origin are generally known to be responsible for most of flash flood events in Malaysia. Flood problems are aggravated by rapid urbanization which modified the hydrological processes of a catchment. This study is aimed to evaluate the characteristic of convective rain in Klang Valley. The characteristics are based on short rainfall interval data between years 2000 and 2004. The convective events were analysed in terms of timing and spatial distribution. The spatial distributions of convective rainfall, derived from meteorological radar data and those observed on the ground are compared. Convective storm occurred most frequently during intermonsoon months which made up about 44%. A variety of storm shape is evident. Most of the convective events occurred over short durations. The convective storms were further classified into slightly convective, moderately convective and strongly convective by using ÃŸ parameter values. A 35 mm/hr threshold intensity is used for separating convective from non convective storms for local conditions. The areal distributions derived from radar and those from raingauge are poorly correlated. Each storm is unique in term of the movement of its storm centre. Some have long paths while others are circling within a limited area. The Aerial Reduction Factor (ARF) obtained from this study is comparable with ARF values obtained earlier by other researchers. A new Intensity Duration Frequency (IDF) curve is plotted based only on convective storms. For a given duration and return period, the new IDF generally results in higher storm intensity compared to the existing IDF curve. However, the new IDF curves are more appropriate for determining design storms for areas experiencing high occurrence of convective events. It is found that, a threshold value of 35 mm/hr could be used in developing IDF of Peak Over Threshold (POT) series.